2004
DOI: 10.1093/occmed/kqh008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a treadmill test for predicting the aerobic capacity of firefighters

Abstract: The Gerkin treadmill protocol overpredicts VO(2max) in healthy men and women and, therefore, should not be used for predicting VO(2max) in individual firefighters, particularly if VO(2max) is a criterion for inclusion or exclusion from duty. At this time, a valid treadmill running test is needed for predicting the VO(2max) value of individual firefighters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 18 publications
3
52
1
5
Order By: Relevance
“…In addition, one in three male firefighters in the current study did not meet a generally accepted minimum cardiorespiratory fitness level of 42.0 mL/kg/min for firefighters (Donovan et al 2009;National Fire Protection Agency 2013;Sothmann et al 1992), even though the VO 2 max values may have been overestimated due to the use of the Gerkin submaximal test (Mier and Gibson 2004). These findings are alarming given that the fire department of the current study has one of the strongest and long-lasting WEFIT programs among US fire departments.…”
mentioning
confidence: 69%
“…In addition, one in three male firefighters in the current study did not meet a generally accepted minimum cardiorespiratory fitness level of 42.0 mL/kg/min for firefighters (Donovan et al 2009;National Fire Protection Agency 2013;Sothmann et al 1992), even though the VO 2 max values may have been overestimated due to the use of the Gerkin submaximal test (Mier and Gibson 2004). These findings are alarming given that the fire department of the current study has one of the strongest and long-lasting WEFIT programs among US fire departments.…”
mentioning
confidence: 69%
“…12 The study design was cross-sectional, and measurement of changes in CIMT over time through a longitudinal study would have been preferable, as risk factors for progression of CIMT have been shown to vary from those predicting CIMT itself. 46 Use of the Gerkin submaximal treadmill test in Phoenix and for Tucson firefighters aged 40 years and younger may have led to overestimation ofVO 2 max , 47 and use of maximal treadmill testing for Tucson firefighters older than 40 years introduced a difference between the two study sites. It is not clear the extent to which these issues affected our ability to accurately assess the effect of MET on CIMT.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in the study of Davies et al (2008), maximum oxygen consumption among male students of emergency care was estimated as 47.9 ml/kg/min (7). Moreover, in other studies by Greg, Michael, Mark, and Mier maximum oxygen consumption was obtained 37 (ml/kg/min), 48 (ml/kg/min), 1.57 (l/min), and 48.8 (ml/kg/min) respectively (811). As the results of these studies show, only the maximum oxygen consumption among staff has been estimated, and few studies have examined how individuals are selected commensurate with job.…”
Section: Introductionmentioning
confidence: 69%